Digital marketing plan for Woo's Pure Feelings - André, Ana Patrícia António (2020)
The goal of this master’s thesis is to define a new digital marketing strategy for a small mediumsized jewellery business in Portugal. This in-company project was conducted with Woo’s Pure Feelings. Woo’s is a jewellery brand that was created in 2006 in Lisbon, Portugal and its goal is to differentiate by transmitting feelings through its products. Currently, there is an increasing need for brands to have a strong digital presence and the use of social platforms is already a requirement to be successful. The use of influencers on social media is the new trend in this new wave of marketing and a need in order to stay relevant in the digital world. In the present time, there is an identified need for improvement in the area of its digital communication for Woo’s Pure Feelings brand and that will be the focus of this project. The plan of this project was built based on; research work such as external situation analysis to evaluate the condition of the industry such as competitors and consumers, an internal analysis to identify the current struggles of the company and define its objectives for the new plan, as well as an online survey to determine the consumer's digital behaviours and preferences, and also interviews with the brand owners and professionals on the industry.